On the Synchronization of Fiscal Policy in Selected ASEAN Countries : New Evidence from Asymmetric Modelling - Chan, Hock Hua; Shirly Siew Ling, Wong; Lew, Yew Kang (2022)
The country’s fiscal deficit and debt levels are still issuing, and governments would always want to solve. Before this, it is very necessary to explore and study the types of fiscal hypotheses in various countries. The types of fiscal hypothesis are tax-spend hypothesis, spend-tax hypothesis, fiscal synchronization and lastly fiscal neutrality. This research aims to access the validity of fiscal hypothesis in five ASEAN countries, namely Malaysia, Indonesia, Philippines, Singapore and Thailand by using time series quarterly data from year 2006 to the first quarter of year 2021. The variables in this study include real gross domestic product (GDP), general government revenue (GR) and general government expenditure (GE). The methodology approach used is the asymmetric modelling approach, which includes Augmented Dickey Fuller test, Kwiatkowski-Phillips-Schmidt-Shin test, bounds test for cointegrating, Autoregressive Distributed Lag and Non-linear Autoregressive Distributed Lag models development and lastly granger causality test. The result from this research is that Malaysia and Thailand support the fiscal synchronization hypothesis, Indonesia and the Philippines support the fiscal neutrality hypothesis, and Singapore supports the spend-tax hypothesis.